Contact electrification and charge distribution on elongated particles in a vibrating container. (24th March 2015) - Pei, Chunlei; Wu, Chuan-Yu; Adams, Michael; England, David; Byard, Stephen; Berchtold, Harald
Abstract: The electrostatic charge can be transferred between particles during collisions. The particle shape plays an important role and, in the current study, the charge accumulation and distribution on elongated particles in a vibrating container are investigated using a discrete element method, in which a contact electrification model is implemented. The elongated particle geometry is modelled using a multi-sphere approach. Five different shapes are considered and characterized using a shape factor, δ, which is defined as the ratio of the difference of the radii between the distal sphere and central sphere to the mean radius of the particle. It is found that the net charge on the central sphere is greater than that on the distal sphere when δ <0. For a particle with δ >0, greater net charge is accumulated on the larger distal sphere. The maximum surface charge difference between the distal and central sphere increases as the shape factor increases. The net charge of the granular system with different particle shapes achieves an equilibrium state during the vibrating process. This accumulating process follows an exponential trend. Graphical abstract: Charge distributions for particles with different shape factors during the container vibration. Highlights: A contact electrification model is applied to analyze the charge transfer process. A multi-sphere method is used to model the elongated particles. Higher net charge is obtained on the larger primary sphere. The maximum surface charge increases with the shape factor.